Six Years at Sea... and Counting : Gulf of Aden Anti-Piracy and China's Maritime Commons Presence - Erickson, Andrew S.; Strange, Austin M. (Book collections on Project MUSE., 2016)
Well over six years of Chinese anti-piracy operations in the Gulf of Aden have directly supported People's Liberation Army Navy (PLAN) modernization goals and provided invaluable experience operating in distant waters. Lessons learned have spawned PLAN innovations in doctrine, operations, and international coordination. Many of the insights gleaned during deployments are applicable to security objectives closer to home; some officers enjoy promotion to important positions after returning. Anti-piracy operations have been a springboard for China to expand considerably its maritime security operations, from evacuating its citizens from Libya and Yemen to escorting Syrian chemical weapons to their destruction and participating in the search for Malaysia Airlines Flight 370. So great are the benefits to China's global maritime presence and enhanced image at home and abroad that when Gulf of Aden anti-piracy operations finally wind down, Beijing will have to develop new means to address its burgeoning overseas interests.